Sensory Integration as a Prerequisite for the Development of Academic Skills in Children - Petrović Lazić, Mirjana D.; Ilić Savić, Ivana S.; Babac, Snežana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The readiness to start school includes the emotional and social maturity of the child. In order for a child to master the demands of the school program as easily as possible, a certain harmony is needed in the development of his abilities. The ability of sensory perception and the ability to integrate sensory stimuli specifically determine the development of reading and writing skills. The aim of this study is to analyze the ability to read and write in hypersensitive and hyposensitive types of sensory integration disorders, with special reference to the analysis of individualization measures in the work with these students in the school system. Disorder of sensory integration is expressed in two basic forms: increased sensitivity (hypersensitivity) and decreased sensitivity (hyposensitivity). In the school system, both forms of sensory integration disorders dominate. Hypersensitivity is manifested by rapid mental fatigue compared to other children. These children have difficulty reading and writing at the same time. They can read a word in many different ways without realizing it. Compared to the hypersensitive child who seems inert, the hyposensitive child is in constant motion, craving additional sensory stimuli in the classroom. These children have great problems with reading and writing figures and symbols such as tables, geometric shapes and musical symbols. Adjusting the teaching material for these children means increasing the font and font color before reading, dividing large-scale tasks into smaller units, using different types of writing pens, constantly emphasizing important units in the lesson, providing a summary of the lesson at the end of the lesson, and occasionally checking the legibility of the handwriting. In this way, students are provided with easier visual, auditory and tactile processing, and therefore more successful writing, reading and understanding of the read material. Thus, a student with sensory processing disorder can achieve academic success, but it is necessary to adapt the curriculum to the appropriate level of sensations.